Peran Perawat dalam Meminimalkan Kecemasan Orang Tua akibat Hospitalisasi Anak di RSU Negara - I Dewa Komang Dharma Putra; I Made Rio Dwijayanto; Ni Luh Ade Kusuma Ernawati (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Pain and hospitalization are the main problems seen in children, if a child is being treated in a hospital, children and parents will be easily anxious. The hospitalization period passed by the child will cause anxiety for himself and his parents. Nurses have an important role in involvement and providing nursing care to patients or families of patients who can affect their health so that they have a higher level of health. Nurses have a role as nurses, patient defenders, educators, coordinators, collaborators, consultants, and reformers. This study includes correlational analytic with the research design used is cross-sectional and sampling uses purposive sampling. Parents whose children experienced hospitalization at the Cempaka State Hospital General Hospital in 2019 were mostly ≥25 years old (92.5%) and were dominated by SMP-SMA as many as 26 (38.8%). A total of 43 respondents (64.2%) said nurses at Cempaka room Negara General Hospital had performed their roles well and 24 respondents (35.8%) said the role of nurses was sufficient. The anxiety of parents whose children are being treated at the Cempaka Room General Hospital in 2019 has a lighter anxiety 43 (64.2%) while respondents with moderate anxiety are 20 (29.9%) and respondents with severe anxiety are as many as 4 (6, 0%). The results of the study stated the value of p = 0,000 (p <0.05) which means there is a relationship between the role of care in minimizing hospitalization for children. There is a significant relationship between the role of nurses by minimizing the anxiety of parents due to the hospitalization of children in the Cempaka room Negara General Hospital 2019.